1984
DOI: 10.1007/bf00052412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on invasion of MO4 mouse fibrosarcoma cells in organ culture

Abstract: Invasion by MO4 mouse fibrosarcoma cells into fragments of embryonic chick heart or lung in organ culture was studied histologically and ultrastructurally at various temperatures between 12 and 40 degrees C. Invasion was absent for at least 7 days at or below temperatures of 29 degrees C. Invasion was invariably observed at or above 30.5 degrees C. Differences in invasion between 29 and 30.5 degrees C could not be ascribed to differences in growth, migration, or microtubule assembly/disassembly of MO4 cells. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…These variations relate to the origin of the host tissue, the presentation of the confronting test cells, and the incubation conditions. Heart fragments from species other than chick 18 , and from tissues such as liver 19 , lung 20 , and brain 21 , have been examined. Instead of aggregates, biopsy specimens , and serum-free confrontations have been shown to be feasible with certain types of cells 25 .…”
Section: Discussionmentioning
confidence: 99%
“…These variations relate to the origin of the host tissue, the presentation of the confronting test cells, and the incubation conditions. Heart fragments from species other than chick 18 , and from tissues such as liver 19 , lung 20 , and brain 21 , have been examined. Instead of aggregates, biopsy specimens , and serum-free confrontations have been shown to be feasible with certain types of cells 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Virally transformed C3H mouse fibroblastic cells [1], which are invasive and metastatic in syngeneic mice [23], are not invasive at temperatures of 29°C or cooler but invade at 30"5°C or higher when cocultured with embryonic chick heart for seven days [9]. Virally transformed C3H mouse fibroblastic cells [1], which are invasive and metastatic in syngeneic mice [23], are not invasive at temperatures of 29°C or cooler but invade at 30"5°C or higher when cocultured with embryonic chick heart for seven days [9].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that invasion in vitro of mouse MO 4 cells [15], of frog Luck~ renal carcinoma explants [19] and of frog PNKT-4B carcinoma cells [20] can be inhibited by lowering the temperature of incubation. In short-term experiments invasion in vitro of MO 4 cells into chick heart showed a transition between 30"5 and 29~ invasion occurred after 4 days of incubation at 30"5~ but not after 7 days at 29~ [15]. As a possible explanation, we considered that absence of invasion was due to alterations in the expression of glycopeptides at the surface of MO 4 cells.…”
Section: Introductionmentioning
confidence: 99%